THE EFFECTIVENESS OF THE ROTATION FOR THE FARMING OF DIFFERENT SPECIALIZATION OF RIGHT-BANK STEPPE OF UKRAINE - Квасніцька, Л. С.; Молдован, В. Г. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
To determine the economically and energetically profitable rotation for the farming of different specialization for the conditions of adequate moisture of Right-Bank Steppe. Field, comparativelycalculated. The highest grain output (5,63t from 1 ha of rotated area) was provided the grain rotation from 100% of grain including 40% of maize for grain with mineral fertilizer system. The release of best feed units (11,9t from the hectare of rotation area) was the typical for the zone yield-changing rotation from 20% of clover for 2 slopes, 20% sugar beets and 60% of grain with organic-mineral fertilizer system. The cheapest feed unit (504,70hrv./t) and high indexes of the energetic effectiveness were received in the rotation saturated with 40% of maize for grain, 40% of alfalfa, 20% of barley in organic fertilizer system. Developing the sowing areas structure it is necessary to consider the correlation between different groups of crops (commodity, grain, technical, feed, etc.) that would provide the increasing of the farming effectiveness, including new elements and principles of rotation building. In today`s energetic crisis when energy prices increases, with the aim of reduce energy and the production cost it is advisable not only to improve the intensive technologies but to conduct the correction of the rotation in the direction of the saturation of plant growing with ``the energetically cheap`` crops. High indexes of the energetic effectiveness provide the rotations with the organic fertilizer system.